Quality assessment of the essential oils from Nardostachys jatamansi (d. Don) dc and Nardostachys chinensis batal obtained from Kathmandu valley market - Paudyal, Mahesh P; Rajbhandari, Meena; Basnet, Purushottam; Yahara, Shoji; Gewali, Mohan B (Scientific World, 2012)
The chemical composition and physicochemical parameters of the essential oils obtained from two species of Nardostachys available in Kathmandu market, N. jatamansi (D. Don) and N. chinensis Batal were determined. GC-MS technique was used for the analysis of the oils. Both oils were characterized by high content of sesquiterpenes. â-gurjunene and jatamansone were the major sesquiterpene components of both oils. Somewhat variation in the amount of chemical components was found in two different species. The physical and chemical parameters such as specific gravity, specific rotation, refractive index and saponification value, acid number, iodine number were very similar for both species. Both oils were, therefore, of comparable quality. Scientific World, Vol. 10, No. 10, July 2012 p13-16 DOI: http://dx.doi.org/10.3126/sw.v10i10.6854